Bipolar Radiofrequency Ablation (Coblation) of External Auditory Canal Lymphatic Malformation and Other Soft Stenoses. (December 2017) - Gu, Alex; Bauman, Nancy M.
Introduction: Soft tissue occlusion of the external auditory canal (EAC) can cause intense pruritis, recurrent foul smelling otorrhea, recurrent otitis externa, and conductive hearing loss. Occlusion of the EAC can be challenging to treat as the area is prone to circumferential scarring. Methods: We describe the novel use of serial bipolar radiofrequency ablation (coblation) to treat 3 children with complete EAC occlusion from congenital and acquired conditions including lymphedema (1), microcystic lymphatic malformation (1), and venolymphatic malformation (1). Results: Patients underwent a mean of 3 procedures with postoperative EAC stenting (7 days) and antibiotic and steroid aural preparations (10 days). Otologic symptoms resolved in all patients, and their EACs remained patent 14 months after last procedure (range, 4-32 months). One patient experienced a pinpoint tympanic membrane perforation that healed spontaneously 2 weeks later. Conclusions: Coblation of soft tissue stenosis of the EAC can be an effective treatment for this problematic condition.